Гідродинаміка багатокомпонентних систем - Драганов, Б. Х. (Енергетика і автоматика, 2017)
UDC 532 (075.8) Hydrodynamics of multicomponent systems B. Draganov The heterogeneous system - heterogeneous structure consisting of different physical properties or chemical components. Examples are heterogeneous aerosols, suspensions, radiation and other components that pollute the environment. They are characterized by the presence of macroscopic irregularities. The purpose of research - to develop a model and find a solution to the dynamics of multi-environment. Materials and methods of research. At the heart of hydrodynamics describe methods of solid heterogeneous environments should proceed with the idea of mixing movement, occupy the same volume. Results. The mechanics of mixtures is based on the physical laws of conservation of mass, momentum and energy. In each of these equations is some divergence flow values, related, at least implicitly, with gradients of thermal, dynamic parameters (so-called thermodynamic forces). There are two ways to obtain linear relations (defining relations) between these flows and paired them thermodynamic forces, based on the macroscopic and kinetic approaches. Kinetic approach associated with generalized solution of the Boltzmann equation for a multicomponent gas mixture to the end designed only for gases of moderate density, known as the potential interaction between elementary particles. The phenomenological approach based on the application of the laws of continuum mechanics and thermodynamics to nonequilibrium macroscopic volume mixture postulate is not associated with a specific microscopic model of interaction of ipidhodyt for a wide class environments. Modeling of multicomponent continuum of different kinds of mixtures as homogeneous and heterogeneous associated with the concept of multi-Continuum and definition of interpenetrating motion components. Considered Continuum is a collection K- Continuum, each of which relates to its component mixture and fill the same volume environment. The phenomenological approach (based on the methods of nonequilibrium thermodynamics), provides a ratio for determining the mass flow and heat as well as convenient algebraic formulas that connect the different coefficients of molecular transport.